Linguistic and non-linguistic prosodic skills in Spanish children with developmental dyslexia. (July 2019) - Calet, Nuria; Gutiérrez-Palma, Nicolás; Defior, Sylvia; Jiménez-Fernández, Gracia
Abstract: Background: The deficit on segmental phonology in developmental dyslexia is well established and according to recent studies this deficit extends to suprasegmental phonology or prosody. However, these studies have focused on word-level prosody. Further research is needed concerning prosodic deficit in dyslexia, especially with a Spanish-speaking population. Aims: The aim of this study was to investigate the role of linguistic (word and phrase-level) and non-linguistic prosodic skills in Spanish children with developmental dyslexia. Method and procedure: 48 Spanish children (8–9 years of age) from ten primary education schools were selected (24 children with developmental dyslexia and 24 chronological age-control children). Non-linguistic rhythm, word and phrase-level prosody, phonological awareness, nonverbal intelligence and reading aloud were assessed. Results: The results obtained show that children with developmental dyslexia scored lower than typically developing readers on non-linguistic rhythm and word and phrase-level prosody tasks. The differences remained statistically significant at the phrase level after controlling for word-level processing (phonological or prosodic), phonological awareness, non-linguistic rhythm and reading skills. Conclusions: Children with developmental dyslexia in Spanish exhibit a core deficit in suprasegmental phonology, at linguistic and non-linguistic levels. The implications of suprasegmental phonology skills for reading acquisition disabilities are discussed.